Petróleo como palanca para el desarrollo económico: analizando las oportunidades y desafíos para la República Cooperativa de Guyana - Clavijo Vitto, William Adrian (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2021)
The article analyzes the opportunities for economic development in Guyana with the rise of its oil industry. To do that, we reviewed the literature on economic development in countries rich in natural resources. Next, the paper discusses the Guyanese experience since the discovery of oil in the Stabroek block and the plans formulated by the government to promote the economic diversification of the country. Based on the above, we analyzed the challenges that Guyana faces to make a correct use of these resources. Among the results, the study shows that even though the increase in oil production will place Guyana among the countries with the highest economic growth in the next decade, it needs to overcome important challenges in terms of institutional capacity, human capital, and infrastructure to ensure an effective use of the wealth derived from oil activities in promoting national development.